On the History of Universities and Medical Faculties - Vasili Razumovskij (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
Speech at the Public Opening of the Nikolay Imperial University at Saratov, December 6, 1909 (Foreword by E.N. Penskaya)